Visual Elements of Kabasaran Character on Web Comic Nusantara Droid War - Dwi Jaya Arisyana; Abay Delon Subarna (Universitas Komputer Indonesia, 2021)
Comics are popular, comics contain stories that are published through images and text and contain information. Comics contain knowledge and entertainment. Comic stories and depictions come from creativity resulting in a variety of stories and visual styles. The visual style and content of the story influenced the interest of the audience and raise many comic genres. Many comics in Indonesia take inspiration from Indonesian culture both from their stories and visualizations. Many research on comics has been carried, but research on the visualization of Indonesian culture in comics is limited, as in previous research is still research on characters and their traits, but many character studies are associated with elements of Indonesian culture. Based on this, research on the content of Indonesian culture in a web comic entitled Nusantara Droid War needs to be carried out. Nusantara Droid War is one of the web comics that contains visualizations of Indonesian culture. The visualization used in this comic uses elements that represent the culture of an Minahasa North Sulawesi. The study aims to find out the cultural elements of North Sulawesi contained in the visualization of the character Droid Kabasaran in the Nusantara Droid War comic. It uses the descriptive qualitative method to describe and visually discover the object of study. The results of the study obtained a visualization of the character of Droid Kabasaran containing visualizations from the Minahasa culture, namely the Kabasaran dance. The visualization of Kabasaran dance elements is obtained from the results of character descriptions, character visuals and character costume elements. The visualization of Kabasaran characters in this comic is shown through skills (abilities) taken from three acts of Kabasaran dance, namely: Cakalele, Kumoyak, and Lalayaan. This research is expected to increase knowledge, increase the amount of research related to character visualization, enrich the science of visual communication design